Ties - Federico Revelli; Tsung-Sheng Tsai (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper investigates whether the rare occurrence of a local election ending in a tie or being decided by a single vote generates informational spill-overs on nearby localities' subsequent elections. First, based on the pivotal-voter theory, we develop a model of costly instrumental voting in sequential elections with private information, where voters update their beliefs regarding the distribution of political preferences and the probability of their vote being decisive upon observing the outcomes in earlier elections, and decide whether to turn out to vote accordingly. Next, by exploiting over a hundred exact ties or one-vote-difference results in Italian mayoral elections during the past two decades and the quasi-experimental conditions created by the staggered municipal electoral calendar, we test the model's empirical predictions and find a substantial impact on voter turnout rates of exposure for geographical reasons to spill-overs from the localities experiencing those bizarre electoral outcomes.
Keywords: D72; H71; 330; tied elections; voter turnout; information spill-over; salience